Study of methoxy-group position influence on compound alm-802 cardiotropic activity - G. V. Mokrov; A. M. Likhosherstov; V. V. Barchukov; V. N. Stolyaruk; I. B. Tsorin; M. B. Vititnova; S. A. Kryzhanovskiy; T. A. Gudasheva (LLC "Publisher OKI", 2019)
A new compound ALM-803 (trihydrochloride N1-(3,4,5-trimethoxybenzyl)-N2-{2-[(3,4,5-trimethoxybenzyl)amino]ethyl}-1,2-ethanediamine) was synthesized as analog of ALM 802, differing from it by the position of the methoxy groups in the phenyl rings. It is established that this structural change leads to the disappearance of anti-ischemic activity and antiarrhythmic activity on the model of aconitine arrhythmia in rats, but the antiarrhythmic activity on models of chloride-calcium arrhythmia and electrical fibrillation of the heart of rats remained (1 mg/kg, intravenously).